Cell Signaling in Neuronal Stem Cells (2018)
The defining characteristic of neural stem cells (NSCs) is their ability to multiply through symmetric divisions and proliferation, and differentiation by asymmetric divisions, thus giving rise to different types of cells of the central nervous system (CNS). A strict temporal space control of the NSC differentiation is necessary, because its alterations are associated with neurological dysfunctions and, in some cases, death. This work reviews the current state of the molecular mechanisms that regulate the transcription in NSCs, organized according to whether the origin of the stimulus that triggers the molecular cascade in the CNS is internal (intrinsic factors) or whether it is the result of the microenvironment that surrounds the CNS (extrinsic factors).